Pregnane derivatives in wheat (Triticum aestivum) and their potential role in generative development - Janeczko, Anna; Oklestkova, Jana; Jurczyk, Barbara; Drygaś, Barbara (Journal of plant research, 2025)
Pregnane derivatives such as pregnenolone or progesterone and many other metabolites are important in mammals where many of them act as hormones including sexual hormones. Much less is known about the presence and functions of pregnane derivatives in plants. The main objectives of this work were (1) to determine the presence of pregnane derivatives in winter wheat (2) verify if there are changes of concentration of pregnane derivatives during wheat growth/development with special attention to vernalisation process (3) to answer the question of whether selected pregnane derivatives are stimulators of wheat development and whether the potential stimulation of this development is accompanied by the expression of the Vrn1 (Vernalisation1) gene. To the best of our knowledge, this is the first report that demonstrates the presence of pregnenolone and 5α-dihydroprogesterone in the leaves and intact crowns of winter wheat. The levels of some of the pregnane derivatives changed during plant growth/development, it was demonstrated that pregnenolone, pregnanolone and 17α-hydroxypregnenolone stimulated wheat development. The changes in the Vrn1 expression are discussed in light of the stimulation of generative development by the pregnane derivatives.
Keywords: Vrn1 expression; 5α-dihydroprogesterone; regulace genové exprese u rostlin; rostlinné proteiny; regulátory růstu rostlin; listy rostlin; Pregnanes; Plant Proteins; pšenice; Triticum; Plant Leaves; Pregnenolone; Plant Growth Regulators; Winter wheat; Vernalisation; pregnany; Cold; Gene Expression Regulation, Plant